2010
DOI: 10.5047/eps.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Velocity structure in the crust beneath the Kyushu area

Abstract: We present high-resolution three-dimensional tomographic images of the crust beneath the entire Kyushu arc, and particularly the western portion. Our results reveal a velocity anomaly that correlates well with an upper crustal gravity anomaly. Signi cant low-velocity anomalies exist beneath the Miyazaki plane and along the Beppu-Shimabara Graben. Another extensive low-velocity region near the bottom of the crust is located just below the volcanic front and between active volcanoes. The low-velocity anomalies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…The earthquakes occurred in a seismically active region of Kyushu known as BeppuShimabara (Unzen), hereafter termed the B-U area, which is characterized by active volcanoes (Aso, Unzen, Kuju, and Tsurumi) and bounded by a shear zone (the western extension of the median tectonic line) to the south. The crustal structure in this region was found to be complex (Saiga et al 2010), with a stress field different from other areas of Kyushu (Matsumoto et al 2015). In this study, we discuss the relationship between the inelastic strain field and the Kumamoto earthquake sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earthquakes occurred in a seismically active region of Kyushu known as BeppuShimabara (Unzen), hereafter termed the B-U area, which is characterized by active volcanoes (Aso, Unzen, Kuju, and Tsurumi) and bounded by a shear zone (the western extension of the median tectonic line) to the south. The crustal structure in this region was found to be complex (Saiga et al 2010), with a stress field different from other areas of Kyushu (Matsumoto et al 2015). In this study, we discuss the relationship between the inelastic strain field and the Kumamoto earthquake sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The data cover the period from January 2000 to July 2013, during which the detectability would be expected to be constant. Saiga et al (2010) and Hori et al (2006) determined earthquake hypocenters in this area using three-dimensional velocity structures. The focal mechanisms were estimated from P-wave polarity data observed at eight or more stations using the HASH algorithm developed by Hardebeck and Shearer (2002).…”
Section: Inelastic Strain In Kyushu Japanmentioning
confidence: 99%
“…The shapes of these two anomalies differ, and one is related to the young portion of the PSP (Shikoku Basin), while the other is associated with the old portion of the PSP. Another 3-D seismic tomography study [Saiga et al, 2010] reported velocity anomalies in the crust beneath Kyushu Island that correlate well with gravity anomalies. A low-velocity anomaly is present in the lower crust at a depth of 30 km beneath the Kyushu Mountains (in the nonvolcanic region), corresponding to the subducted KPR, which is buoyant.…”
Section: Introductionmentioning
confidence: 98%
“…[2000] discussed the Another seismic tomography imaging study [Saiga et al, 2010] has revealed a low-velocity anomaly in the lower crust at a depth of 30 km beneath the Kyushu Mountains, which corresponds to the subducted KPR (which is buoyant) between the Shikoku Basin and the old PSP. This region of the Kyushu Mountains has no active volcanoes (Figure 1).…”
Section: 1002/2014jb011336mentioning
confidence: 99%
See 1 more Smart Citation